Płód/ dziecko z zespołem wad letalnych: od diagnozy do końca życia. Doświadczenia personelu medycznego oraz rodziców w ramach perinatalnej opieki paliatywnej - Gruca-Stryjak, Karolina; Łuczak-Wawrzyniak, Jadwiga; Borkowska-Kłos, Monika (Człowiek i Społeczeństwo, 2024)
Epidemiological studies indicate a significant risk of congenital malformations in about 2–3% of pregnancies, rising to 20% for perinatal deaths associated with polyposis. Approximately 15% of all congenital anomalies have a genetic background, some of which have serious clinical consequences. Modern prenatal diagnostic methods allow increasingly precise examination of the fetus, including ultrasound, biochemical tests, and analysis of extracellular DNA in the mother’s blood. This paper presents the experiences of medical staff and parents in the care of fetuses with adverse prenatal diagnoses, focusing on the provision of perinatal palliative care. A retrospective analysis of clinical cases and a questionnaire survey of medical staff were conducted at the Gynecological-Obstetric Clinical Hospital of the Medical University of Poznan. The results show that approximately 7–9% of patients with an unfavorable prenatal diagnosis receive perinatal palliative care. The survey of medical staff shows the different experiences of palliative care in childbirth and the importance of the birth plan for doctors and midwives. These findings may help to improve the quality of medical care for fetuses with fatal defects and better integrate medical staff into the perinatal care process.